Keragaman ikan di Danau Cala, Kabupaten Musi Banyuasin Sumatera Selatan - Jifi Abu Ammar; Mohammad Mukhlis Kamal; Sulistiono . (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2014)
The aim of his studi was to evaluate the fish fauna in Danau Cala in dry season, transition season, and the tide season. The survey was conducted 3 times on July 2013, October 2013 and January 2014 as representative of dry, transition and tide seasons. The fish sampling was conducted by gillnets and fish traps. A total of 35 fish species were recorded during the study; 23 species in dry season, it was dominated by tembakang fish (Helostoma temminckii) from family Helosmatidae, Sepat siam fish(Trichogaster pectoralis) from Belontiidae family, and snakehead fish (Channa striata) of Channidae family. A total of 16 species were recorded on transitional seasons where baung fish (Hemibagrus nemurus) of the family Bagridae, and seluang fish (Rasbora sp) of the family Cyprinidae were predominant. In addition, 15 fish species were recorded on tide season which was dominated by baung fish (Hemibagrus nemurus) and tendon fish (Mystus sabanus) of family Bagridae